Perspektif Sound Governance Dalam Tata Kelola Penempatan Pekerja Migran Indonesia: Kasus Pekerja Perempuan Domestic Worker - Wuryandari, Ratna Dewi (Journal of Governance and Administrative Reform, 2021)
AbstractOne of the consequences of globalization for Indonesia is the migration of Indonesian workers abroad, especially women in low-ranking domestic workers. Globalization demands changes in governance (governance). The quality of governance is inseparable from the quality of public management. Changes due to globalization in all fields increase the interdependence and interconnection among all countries in the world today, as well as the placement of Indonesian migrant workers abroad. From various studies conducted, it is found that the placement of Indonesian migrant workers presents the presence of international actors in the migration process. Many facts reveal that the migration industry as an international actor has a stronger power relation role in determining the migration process and holds control in the recruitment process for prospective Indonesian migrant workers. This study tries to analyze from the perspective of the concept of sound governance where to produce good governance, the dimensions of sound governance need to be a support in the implementation of the placement of migrant workers. From the results of case analysis by comparing various studies on the placement of Indonesian migrant workers, it is found that currently, the Government in managing the placement of migrant workers has not implemented a sound governance perspective. Furthermore, in order to improve governance, the dimensions of sound governance offered in this paper can be a step in improving all aspects of the placement of Indonesian migrant workers.Keywords: sound governance, governance, Indonesian migrant workersAbstractSalah satu konsekuensi dari globalisasi bagi Indonesia adalah adanya arus migrasi tenaga kerja Indonesia ke luar negeri khususnya perempuan pada jabatan rendah domestic worker. Globalisasi menuntut perubahan tata kelola dalam pemerintahan (governance). Kualitas tata kelola tidak terlepas dari kualitas manajemen public. Perubahan akibat globalisasi di segala bidang meningkatkan saling ketergantungan dan interkoneksi di antara semua negara di dunia saat ini, demikian juga dengan penempatan pekerja migran Indonesia ke luar negeri. Dari berbagai penelitian yang dilakukan, ditemukan fakta bahwa penempatan pekerja migran Indonesia menghadirkan adanya actor-actor internasional dalam proses migrasi. Banyak fakta mengungkap bahwa Industri migrasi sebagai actor internasional memiliki peran relasi kuasa yang lebih kuat dalam menentukan proses migrasi serta memegang kendali dalam proses rekruitmen calon pekerja migran Indonesia. Penelitian ini mencoba menganalisis dari perspektif konsep sound governance dimana untuk menghasilkan tata kelola yang baik, dimensi-dimensi sound governance perlu menjadi dukungan dalam pelaksanaan penempatan pekerja migran. Dari hasil analisis kasus dengan membandingkan berbagai penelitian tentang penempatan pekerja migran Indonesia, ditemukan fakta bahwa saat ini, Pemerintah dalam mengelola penempatan pekerja migran belum menerapkan perspektif sound governance. Lebih lanjut untuk melakukan pembenahan tata kelola, dimensi-dimensi sound governance yang ditawarkan dalam tulisan ini dapat menjadi tahapan dalam melakukan pembenahan dari segala aspek penempatan pekerja migran Indonesia.Kata kunci: sound governance, tata kelola, pekerja migran Indonesia